The Effectiveness of e-LKPD Sience Based on Project Based Learning in Improving Critical Thinking Skills of Junior High School Students - Anggraeni, Riska Ahwa; Mahardika, I Ketut (International Journal of Education, Information Technology, and Others, 2026)
This study aimed to examine the effectiveness of an electronic student worksheet (e-LKPD) based on Project Based Learning (PjBL) on temperature and heat material in improving junior high school students’ critical thinking skills. The study employed a research and development approach using the ADDIE model, which consists of the stages of Analyze, Design, Develop, Implement, and Evaluate. The e-LKPD was validated by three experts to determine its validity, practicality, and feasibility before implementation. The implementation was conducted in class VII-F of SMPN 2 Jember. Data were collected through expert validation sheets, student response questionnaires, and critical thinking skill tests administered in the form of pretests and posttests. The results showed a significant improvement in students’ critical thinking skills after the implementation of the PjBL-based e-LKPD. The average pretest score increased from 55 to 88.75 in the posttest, with an N-Gain value of 0.75, categorized as high. Indicator-based analysis revealed that all critical thinking indicators improved, with the evaluation indicator achieving the highest N-Gain value of 0.87. These findings indicate that the PjBL-based e-LKPD is effective in enhancing students’ critical thinking skills and supporting active, meaningful science learning. Therefore, the PjBL-based e-LKPD can be used as an effective alternative learning material for teaching temperature and heat in junior high schools